Treatment of Spleen-Deficiency Syndrome With Atractyloside A From Bran-Processed Atractylodes lancea by Protection of the Intestinal Mucosal Barrier - Tu, Jiyuan; Xie, Ying; Xu, Kang; Qu, Linghang; Lin, Xiong; Ke, Chang; Yang, Desen; Cao, Guosheng; Zhou, Zhongshi; Liu, Yanju (Frontiers in Pharmacology, 2020)
Atractylodes lancea (Thunb.) DC (AL) is used in traditional Chinese medicine for the treatment of spleen-deficiency syndrome (SDS). Bran-processed Atractylodes lancea (BAL) has been found to be more effective than unprocessed Atractylodes lancea. However, the compound in BAL active against SDS remains unclear. The pharmacological efficacy of BAL and its mechanism of action against SDS were investigated by HPLC-ELSD. Candidate compound AA (atractyloside A, AA) in AL and BAL extracts was identified by HPLC-MS analysis. AA was tested in a rat model of SDS in which body weight, gastric residual rate, and intestinal propulsion were measured, and motilin (MTL), gastrin (GAS), and c-Kit quantified by enzyme-linked immunosorbent assay. Potential targets and associated pathways were identified based on network pharmacology analysis. mRNA expression levels were measured by qRT-PCR and protein expression by Western blot analysis and immunohistochemistry. AA increased body weight, intestinal propulsion, MTL, GAS, and c-Kit levels, while decreasing gastric residual volume and intestinal tissue damage, while EGFR and PCNA levels remained the same. Seventy-one potential pharmacologic targets were identified. Analysis of protein interaction, GO functional analysis, pathway enrichment analysis, and docking and molecular interactions highlighted MAPK signaling as the potential signal transduction pathway. Validation experiments indicated that treatment with AA increased MTL, GAS, ZO-1, and Ocln levels while reducing AQP1, AQP3, and FGF2 levels. In addition, phosphorylation of p38 and MLCK expression were inhibited. AA improved gastrointestinal function by protecting the intestinal mucosal barrier via inhibition of the p38 MAPK pathway. The results have clinical implications for the therapy of SDS.